Research on the dispersion of carbon fiber and recycled carbon fiber in cement-based materials: a review - Gao, Han; Xia, Yanghao (Frontiers in Materials, 2023)
Recycled carbon fiber, as a novel form of regenerated fiber, exhibits exceptional properties such as high strength, high modulus, excellent electrical conductivity, and corrosion resistance. Consequently, it has garnered significant attention in recent years, owing to its potential to confer unique intelligent characteristics to cement-based materials. However, the dispersion of recycled carbon fiber remains an inevitable concern. Building upon existing research, this paper meticulously categorizes different types of recycled carbon fiber based on their mechanical properties and surface characteristics, while also exploring the impact of additives on fiber dispersion. Furthermore, a thorough evaluation of fiber dispersion methods is provided, considering the dimensions of stability, uniformity, and morphology at various stages, including fiber suspension, fresh mixture, and hardened matrix. Additionally, this paper offers a comprehensive summary and comparison of fiber dispersion methods, taking into account fiber pretreatment and preparation processes. Extensive literature reviews unequivocally support the notion that achieving a uniform dispersion of recycled carbon fiber serves as a fundamental requirement for enhancing and optimizing the properties of composites. Consequently, the utilization of dispersion and evaluation methods based on carbon fiber enables the exploration of appropriate dispersion methods tailored to different types of recycled carbon fiber in cement-based materials.